1994
DOI: 10.2527/1994.7251204x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of somatotropin on myosin expression in pigs1

Abstract: Daily administration of recombinant porcine somatotropin (rpST) has marked effects on growth performance of swine. Protein accretion rates are dramatically increased with rpST treatment. However, the effect of rpST on specific muscle proteins has not been addressed. The purpose of this study was to examine the effects of rpST on 1) the distribution pattern of isomyosins, 2) the total myosin heavy chain protein levels, and 3) myosin heavy chain mRNA abundance present in swine skeletal muscle. There were no diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…This is in agreement with previous findings obtained by using histochemical staining (Solomon et al, 1988 and1990;Beermann et al, 1990;Ono et al, 1995;Sorensen et al, 1996) and by directly measuring the mRNA and protein levels of MyHC isoforms (Czerwinski and Martin, 1994). However, there have been some controversial results reported by Solomon et al (1991) who found that at the body weight of 60 and 90 kg, LD muscle of pigs injected with 100 mg/kg per day pGH from 30 to 60 kg possessed of more oxidative-glycolytic fibres and fewer glycolytic fibres.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with previous findings obtained by using histochemical staining (Solomon et al, 1988 and1990;Beermann et al, 1990;Ono et al, 1995;Sorensen et al, 1996) and by directly measuring the mRNA and protein levels of MyHC isoforms (Czerwinski and Martin, 1994). However, there have been some controversial results reported by Solomon et al (1991) who found that at the body weight of 60 and 90 kg, LD muscle of pigs injected with 100 mg/kg per day pGH from 30 to 60 kg possessed of more oxidative-glycolytic fibres and fewer glycolytic fibres.…”
Section: Discussionsupporting
confidence: 92%
“…Compared with its well-defined positive effect on myofibre hypertrophy, the influence of rpGH on myofibre-type composition is still under debate. Many studies reported that exogenous GH had no effect on the skeletal muscle fibre composition (Solomon et al, 1988 and1990;Beermann et al, 1990;Czerwinski and Martin, 1994), while some experiments -E-mail: zhao.ruqian@gmail.com demonstrated divergent results (Solomon et al, 1991 and.…”
Section: Introductionmentioning
confidence: 99%
“…Lys, threonine, methionine, tryptophan, and valine are currently available in crystalline form and can be supplemented in the diet to eliminate excess AA such as Leu. Because myosin is the most abundant protein in muscle (Czerwinski and Martin, 1994), its expression can be used as indicator of protein synthesis in pigs. The objective of the present study was to analyze the effect of different Leu:Lys ratios on the expression of the cationic AA transporters b 0,+ and CAT-1 in the jejunum, liver, longissimus dorsi (LD) muscle, and semitendinosus (ST) muscle, the expression of myosin in LD and ST, and the availability of AA (serum concentration, SC).…”
Section: Introductionmentioning
confidence: 99%
“…According to Czerwinski and Martin (1994), myosin is the most abundant protein in muscle cells, and the isoform IIB accounts for about 80% of the total fibers in some pig muscles; this isoform is extensively expressed in LM and SM (Lefaucheur et al, 2002). Furthermore, Brodsky et al (2004) found that low intake of dietary protein reduced the synthesis of myosin in human, suggesting that myosin can be a good indicator of protein synthesis and accretion in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Type IIB fibers account for about 80% of the total fibers in some pig muscles (Czerwinski and Martin, 1994) and are extensively expressed in LM and SM of pigs (Lefaucheur et al, 2002). Also, a housekeeping 18S rRNA (GenBank AY265350) was used as an endogenous control to normalize variations in mRNA.…”
Section: Reverse Transcriptionmentioning
confidence: 99%